The ‘End’ of the Maya Long Count? 2012 and the Classic Maya (Altre Modernità, 2013)
The second meeting of the AISI (Associazione Italiana Studi Iberoamericani) was dedicated to “Apocalypse” in Latin American literature. In the year of 2012 this particular subject was chosen as various non- and pseudo-scientific and New Age publications hold that the Maya Long Count ends in 2012, more specifically on December 21. In this essay I present a short overview on how the idea of an ‘end’ of the Maya Long Count emerged, which ancient Maya hieroglyphic texts (from the Late Classic Maya period, ca. A.D. 550-900) refer to this particular date, and what the only text (from the site of Tortuguero, Tabasco, Mexico) that may tell us something on 2012 reveals. I also present a short historic overview of the quality of the drawing of the Tortuguero text and how these influenced earlier decipherments, translations, and interpretations of this text. Ultimately, the hieroglyphic text itself is analyzed and one detail is discusses in more detail, the verb root tzutz- and which different, but not necessarily mutually exclusive, meanings it has in Mayan languages.